Lithium enrichment in the Qarhan Salt Lake (China) was a long-term process driven by interglacial-glacial cycles - Pengyu Long; Yanjun Zhao; Xiaohong Sun; Ik Woo; Jiangmin Du; Yufei Hu; Wanping Liu; Ju Jiao; Lisheng Wang (Communications Earth & Environment)
Abstract Qarhan Salt Lake, China’s largest brine-type potassium-lithium deposit, holds substantial economic value. However, the timing of lithium-rich brine formation, its origin, and the role of climate in its development remain unclear. This highlights the need for a deeper understanding of salt lake evolution, particularly regarding ore-forming brine composition and the palaeoclimate. Therefore, we conducted 230Th dating on halite deposits from borehole ZK6-7 (7.5–46.7 metres) in the northern Bieletan, revealing halite deposition at 237.79–30.29 thousand years before 2000 A.D. The maximum homogenisation temperature of fluid inclusions was 23.9–41.7 °C, indicating frequent palaeobrine temperature fluctuations, corresponding to palaeoclimatic events in the Qinghai–Tibet Plateau and Qaidam Basin. Lithium, potassium, magnesium, boron, and bromine concentrations were inversely correlated with the maximum homogenisation temperature. Lithium-rich brine formation in the Bieletan was a long-term process driven by interglacial-glacial cycles, where warm periods increased river flow and material supply, while dry-cold periods intensified evaporation, promoting mineral enrichment.